Pengaruh Pembiayaan Terhadap Kesejahteraan Nasabah Melalui Peran Pt Permodalan Nasional Madani (PNM) Mekaar Sebagai Variable Intervening Di Klalin I Aimas Kabupaten Sorong - Hindun Mahiroh; Hasbiah; Fitrah Ariyani (Prodi Ekonomi Syariah IAIN Sorong, 2025)
The limited access to capital for Micro, Small, and Medium Enterprises (MSMEs), particularly for micro-businesses run by women in areas like Sorong Regency, is a major challenge in economic development. This study aims to examine the real effect of PNM Mekaar financing (X) and its role (Z) on the welfare of women customers (Y) in Klalin 1 Aimas, Sorong Regency. This research uses an associative quantitative approach (correlation) with a positivist paradigm. The research sample consists of 50 active customers. Data analysis employs the Partial Least Square-Structural Equation Modeling (PLS-SEM) method using SmartPLS software. The results of the analysis indicate the following: The effect of Financing (X) on Welfare (Y) is highly significant and positive. This finding confirms that access to capital is a key and most effective factor in improving customer welfare. The effect of Financing (X) on the PNM Mekaar Role (Z) is nearly significant. The PNM Mekaar Role (Z) does not have a significant effect on Welfare (Y). Overall, 61.1% of the variation in customer welfare can be explained by this model. PNM Mekaar financing directly serves as the primary instrument in enhancing customer welfare. However, the effectiveness of the mentoring and training role needs to be thoroughly evaluated and its quality improved. Conclusion and Suggestion PNM Mekaar is recommended to review the design of the mentoring program, the relevance of the material, and the capacity of the Account Officers (AO) to provide significant added value for the customers. Would you like me to translate another paragraph or perhaps clarify any specific terms used in this abstract